Microglial reactivity in brainstem chemosensory nuclei in response to hypercapnia - Eugenín, Jaime; Beltrán-Castillo, Sebastián; Irribarra, Estefanía; Pulgar-Sepúlveda, Raúl; Abarca, Nicolás; von Bernhardi, Rommy (Frontiers in Physiology, 2024)
Microglia, the resident immune cells of the CNS, surveil, detect, and respond to various extracellular signals. Depending on the nature of these signals, an integrative microglial response can be triggered, resulting in a phenotypic transformation.Here, we evaluate whether hypercapnia modifies microglia phenotype in brainstem respiratoryrelated nuclei. Adult C57BL/6 inbred mice were exposed to 10% CO2 enriched air (hypercapnia), or pure air (control), for 10 or 30 min and immediately processed for immunohistochemistry to detect the ubiquitous microglia marker, ionized calcium binding adaptor molecule 1 (Iba1).Hypercapnia for thirty, but not ten min reduced the Iba1 labeling percent coverage in the ventral respiratory column (VRC), raphe nucleus (RN), and nucleus tractus solitarius (NTS) and the number of primary branches in VRC. The morphological changes persisted, at least, for 60 min breathing air after the hypercapnic challenge. No significant changes were observed in Iba1+ cells in the spinal trigeminal nucleus (Sp5) and the hippocampus. In CF-1 outbred mice, 10% CO2 followed by 60 min of breathing air, resulted in the reduction of Iba1 labeling percent coverage and the number and length of primary branches in VRC, RN, and NTS. No morphological change was observed in Iba1+ cells in Sp5 and hippocampus. Double immunofluorescence revealed that prolonged hypercapnia increased the expression of CD86, an inflammatory marker for reactive state microglia, in Iba1+ cells in VRC, RN, and NTS, but not in Sp5 and hippocampus in CF-1 mice. By contrast, the expression of CD206, a marker of regulatory state microglia, persisted unmodified. In brainstem, but not in hippocampal microglia cultures, hypercapnia increased the level of IL1β, but not that of TGFβ measured by ELISA. Our results show that microglia from respiratory-related chemosensory nuclei, are reactive to prolonged hypercapnia acquiring an inflammatory-like phenotype.